2013
DOI: 10.5114/pjp.2013.39333
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of CXCR4 and γ-catenin expression pattern in breast cancer subtypes and their relationship to axillary nodal involvement

Abstract: Chemokine receptor 4 (CXCR4) and γ-catenin are known to play an important role in development of metastasis in breast cancer. However, there is not enough information about these biological markers' distribution in different breast cancer subtypes, or their relationship to lymph node metastases in each subtype. In this study, staining characteristics of CXCR4 and γ-catenin were analyzed in each breast cancer subtype and their relationship to lymph node involvement explored. There was a statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Earlier, we reported a correlation between cytoplasmic CXCR4 expression and lymph node metastasis, especially in HER2+ and basal-like triple-negative breast cancer patients, thus supporting the similar observations reported by others as well [20]. Furthermore, Zhang et al have reported more pronounced expression of CXCR4 in basal-like triple-negative subtype than in Luminal A [21].…”
Section: Discussionsupporting
confidence: 91%
“…Earlier, we reported a correlation between cytoplasmic CXCR4 expression and lymph node metastasis, especially in HER2+ and basal-like triple-negative breast cancer patients, thus supporting the similar observations reported by others as well [20]. Furthermore, Zhang et al have reported more pronounced expression of CXCR4 in basal-like triple-negative subtype than in Luminal A [21].…”
Section: Discussionsupporting
confidence: 91%
“…1a ) ; 2+ = 26–75% of cells; and 3+ = >75% of cells ( Fig. 1b ) [23]. Plakoglobin expression was considered high if the score was 3, and low when score was ≤2.…”
Section: Methodsmentioning
confidence: 99%
“…It is enabled by determination of chemokine receptor 4 (CXCR4) expression. Elevated CXCR4 expression was found in 90% (in HER2-positive breast cancer) to 78.5% of patients (luminal A type of cancer) with metastases to the axillary fossa [33]. Use of tests determining the degree of expression of selected gene panels may also be helpful [34,35].…”
Section: Discussionmentioning
confidence: 99%